Isolation, detection and genomic differentiation of escherichia coli from aquatic environments in Kelantan, Malaysia - Rathi, A.; Thong, Kwai Lin; Chong, V.C. (Faculty of Science, University of Malaya, 2009)
The main aims of this study were to isolate and detect the presence of pathogenic E. coli in selected aquatic environments in Bachok, Kelantan, as well as to determine the presence of their virulence genes and the genomic diversity among the isolates. Fifty water samples from various aquatic environments of Bachok, Kelantan were examined for total coliform and pathogenic E. coli. The presence of total coliform was significantly correlated to E. coli (p<0.05). Among the putative E. coli, 176 isolates retrieved from selective media, 116 (66) from 29 water samples were positive for biochemical tests and harbored the phoA gene, which is the housekeeping gene for E. coli. A hexaplex PCR was performed to detect six virulence genes in pathogenic E. coli such as heatstable toxin 1 (ST1), heat-labile toxin 1 (LT1), heat-labile toxin 2 (LT2), verotoxin1 (VT1), verotoxin 2 (VT2) and attachment and effacement (eaeA). Isolates from only one sample harbored the ETEC as the isolates were positive for the LT1-heat labile toxin. Antimicrobial susceptibility tests showed that only ETEC isolates was resistant to ampicillin, chloramphenicol and trimethoprim-sulfamethoxazole. The rest of E. coli isolates were susceptible to the tested antibiotics. The analysis of genomic diversity of 116 E. coli isolates by Repetitive Extragenic Palindromic (REP)-PCR generated 27 patterns (F=0.26-1.0). The REP-PCR profiles were reproducible and the multiple DNA fingerprints showed that the E. coli isolates were genetically diverse. A dendrogram generated by the UPGMA algorithm showed 4 clusters of E. coli isolates based on 80 similarity. Overall, REP-PCR generated high genetic variability within the E. coli isolates. REP-PCR is a promising molecular method for determining the genomic diversity of environmental E. coli strains.